2022
DOI: 10.3389/fped.2022.916184
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Development of Immunity and Allergic Diseases in Farming and Non-farming Lifestyle Infants: Design, Methods and 1 Year Outcomes in the “Zooming in to Old Order Mennonites” Birth Cohort Study

Abstract: Traditional farming lifestyle has been shown to be protective against asthma and allergic diseases. The individual factors that appear to be associated with this “farm-life effect” include consumption of unpasteurized farm milk and exposure to farm animals and stables. However, the biomarkers of the protective immunity and those associated with early development of allergic diseases in infancy remain unclear. The “Zooming in to Old Order Mennonites (ZOOM)” study was designed to assess the differences in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Our analysis captured key overlapping markers between OOM versus ROC with or without AD, such as SNX5 and IL17D, and distinct markers as shown in OOM infants bathed less frequently than ROC (p <.05). 2 We found highly significant correlations between bathing frequency and skin biomarkers related to asthma severity, such as RNF182, SEPTIN1, and SCN7A, as well as those implicated in asthma, AD, or Th2 allergic inflammation, including LRTM1 and CSF1R (all r >0.85 and p <.05; Table S3). 12 We also observed significant negative correlations with Th2 suppressive marker BACH2 (r =−0.9) and skin barrier maintenance markers (GRHL1, PDCD6IP, r = −0.8) (all p <.05; Table S3).…”
Section: Skin Tape-strips In Old Order Mennonite Toddlers Reveal Upre...mentioning
confidence: 82%
See 2 more Smart Citations
“…Our analysis captured key overlapping markers between OOM versus ROC with or without AD, such as SNX5 and IL17D, and distinct markers as shown in OOM infants bathed less frequently than ROC (p <.05). 2 We found highly significant correlations between bathing frequency and skin biomarkers related to asthma severity, such as RNF182, SEPTIN1, and SCN7A, as well as those implicated in asthma, AD, or Th2 allergic inflammation, including LRTM1 and CSF1R (all r >0.85 and p <.05; Table S3). 12 We also observed significant negative correlations with Th2 suppressive marker BACH2 (r =−0.9) and skin barrier maintenance markers (GRHL1, PDCD6IP, r = −0.8) (all p <.05; Table S3).…”
Section: Skin Tape-strips In Old Order Mennonite Toddlers Reveal Upre...mentioning
confidence: 82%
“…1 Research has shown that children raised on farms experience lower rates of atopic conditions, with serum-based studies suggesting an association between early life environmental exposure and distinct immune development patterns. [2][3][4][5] Nevertheless, there is limited insight into how farming lifestyle may impact skin biomarker expression and protect against atopy. Old Order Mennonites (OOM) are among the rural communities that have been studied, and comparisons with the geographically adjacent urban Rochester (ROC) population suggest a protective role of rural living against atopic development.…”
Section: Skin Tape-strips In Old Order Mennonite Toddlers Reveal Upre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional farming lifestyle and urban lifestyle mothers in this cohort were recruited from the Old Order Mennonite (OOM) population of western New York and suburban/urban Rochester, NY, respectively. OOM mothers are known to have increased rates and duration of breastfeeding in comparison to their urban lifestyle counterparts 17 , 18 . Cryopreserved HM samples were thawed and milk fat and cells were eliminated from HM samples using differential centrifugation followed by filtration through a 0.22 μm filter.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional farming lifestyle and urban lifestyle mothers in this cohort were recruited from the Old Order Mennonite (OOM) population of western New York and suburban/urban Rochester, NY, respectively. OOM mothers are known to have increased rates and duration of breastfeeding in comparison to their urban lifestyle counterparts (12,13). All participants were recruited after written informed consent.…”
Section: Isolation Of Human Milk Supernatantsmentioning
confidence: 99%